Advocate interaction with clients in providing criminal legal aid in Jambi region - Abdullah, Said (Future Academy www.FutureAcademy.org.UK, 2018)
In the criminal justice process Advocate interaction in providing legal aid services has begun since suspect heard his statement in front of the investigator, the process of assisting the suspect/defendant by advocate not in accordance with the law, because at the time Advocate wants to run his profession in criminal law enforcement and when dealing with police, prosecutors and judges often face obstacles. There are two legal issues found; First: How is advocate's interaction to provide legal assistance in according to Law Number 16 Year 2011 and Law Number 8 Year 2003 contributes to the underprivileged? Second; Are there any obstacles in implementing advocate interaction in criminal law enforcement in Jambi region. This research is done normatively and empirically to answer the problems. The temporary conclusions obtained in this study are; First; Not optimal interaction between Advocate and client in providing legal aid services when in accordance with the law. Second; Obstacles in the implementation of Advocate interaction with the Client due to initial inspection is passive and facultative,investigators do not convey the rights of suspects, and the limited number of lawyers who provided free legal assistance by the Ministry of Justice and Human Rights and the defendants did not understand their rights. The implications of these obstacles will become the difficulty of justice which is the difficulty for the economically disadvantaged society to access justice.